TAHAPAN PENDIDIKAN SEKS DALAM KAJIAN PSIKOLOGI DAN AL-QUR’AN - Hilyati Aulia; Izza Himawanti (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2020)
The issue of sex has always been a hot theme to discuss in both the academic and public sphere. Basically, sex education is an effort to guide and nurture a person to understand sex knowledge correctly and be able to channel it properly. This article aims to explain the stages of sex education in the study of psychology in the concept of the Qur'an and explain its application which has been described in detail in the Qur'an. The method used in the study of this article is description-literacy with a hermeneutical-psychological approach. The results of the study of the Koran at the stage of sex education according to the psychological stage are as follows: the oral phase focuses on forming closeness and feeling of comfort in children. The anal phase focuses on teaching genitalia, cleanliness and purification. The phallic phase focuses on identifying each sex and its role gender plays in society. The latent phase is an important part for parents to re-build closeness to children on a more equal and intimate level to children. And the genital stage as the main part of providing complete sexual education, including about the relationship of the opposite sex in accordance with Islamic norms and rules.